Conservation agriculture for productivity and profitability of wheat and lentil in maize based cropping system in far western Nepal: Conservation agriculture for wheat and lentil (Journal of the Bangladesh Agricultural University, 2018)
Zero tillage with crop residue retention which is principle of conservation agriculture (CA) can be a good practice to achieve sustainable and profitable crop yield without affecting soil fertility. This approach was not tested in wheat and lentil based maize-mungbean system in far western Nepal. The effect of CA in the maize-wheat-mungbean and maize-lentil-mungbean cropping systems with two varieties of each of wheat and lentil was studied at Regional Agricultural Research Station, Bhagetada, Dipayal, Doti district of Nepal for two years (2015 and 2016).  The average grain yield of wheat and lentil under the CA system was 5.92% higher (2.86 t ha−1) than that of conventional agriculture (2.70 t ha−1). The CA under maize-wheat-mungbean cropping system produced 7.90% higher grain yield (4.78 t ha−1) compared to conventional agriculture and the CA under maize-lentil-mung bean cropping system gave11.11% higher grain yield (1.00 t ha−1). Maize-wheat-mungbean cropping system, conservation agriculture and WK 1204 variety of wheat produced 9.34% higher yield (4.80 t ha−1) than conventional agriculture whereas maize-lentil-mungbean cropping system, conservation agriculture and Khajura1 variety of lentil recorded 11.96% higher grain yield (1.03 t ha−1) than conventional agricultural. The CA system produced 114% higher net benefit (NRs. 40200 ha−1) than that of conventional agriculture. Higher yields of crops in CA system could be associated with improvement of soil properties for minimum soil disturbance and residue retention and profitable yield for reduced cost of production. Thus, the 2-year study suggests that no tillage with previous crop residues retention and use of higher yielding varieties is a potential crop cultivation approach for the maize based cropping system in light textured soil of river basin area of Nepal in order to sustain soil health, crop yield and farm economy.J. Bangladesh Agril. Univ. 16(3): 403–410, December 2018